Evaluation of Particle Size Dependent Crystal Defects in Inconel 718 by Line Profile Analysis of X-ray Diffraction - Azersky, Colby. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Douglas Matson, Sangho Jeon, and Peggy Cebe.; Keyword: Mechanical engineering.; The purpose of this study is to investigate the relationship between metallic powder particle size and the associated density of atomic line defects within the crystal lattice. This relationship, as it relates to undercooling during solidification, will increase the fidelity of computational models in industrially important molten metal processes such as casting and welding. Experiments at both MIT and Tufts facilities show a trend of increased dislocation density with decreased particle size. Industrially important Inconel 718 metallic powder was sieved into a smaller particle diameter size range of 20-25µm and a larger range of 38-45µm. Line profile analysis of X-ray diffraction patterns of the smaller particle sample group show a 22.5% and 125% increase in dislocation density at the MIT and Tufts facilities, respectively.